Contemporary Clinical Treatment Options and Outcomes of Aortic Valve Disease: Integrating Modern Insights into a Cohesive Therapeutic Paradigm - Mladen J. Kočica (Journal of Cardiovascular Development and Disease, 2025)
Historically, the aortic valve (AV) was seen as a passive mechanical structure facilitating unidirectional blood flow by opening and closing in response to pressure changes, with little or no biological activity [...]